2010
DOI: 10.1007/s11661-009-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Cyclic Deformation Behavior of a Friction-Stir-Welded 7075 Al Alloy

Abstract: Microstructural changes and cyclic deformation characteristics of friction-stir-welded 7075 Al alloy were evaluated. Friction stir welding (FSW) resulted in significant grain refinement and dissolution of g¢ (Mg(Zn,Al,Cu) 2 ) precipitates in the nugget zone (NZ), but Mg 3 Cr 2 Al 18 dispersoids remained nearly unchanged. In the thermomechanically affected zone (TMAZ), a high density of dislocations was observed and some dislocations were pinned, exhibiting a characteristic Orowan mechanism of dislocation bowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 59 publications
5
65
0
Order By: Relevance
“…1-Schematic illustration of friction-stir-welded 6061Al-T651 joints showing fatigue specimen machining, microindentation hardness test path, and various zones (BM, HAZ, TMAZ, and NZ) across the weld. [32] *JEOL is a trademark of Japan Electron Optics Ltd., Tokyo, Japan. section of 32 9 6 9 5.6 mm in size, were machined perpendicular to the FSW direction, as indicated in Figure 1.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Schematic illustration of friction-stir-welded 6061Al-T651 joints showing fatigue specimen machining, microindentation hardness test path, and various zones (BM, HAZ, TMAZ, and NZ) across the weld. [32] *JEOL is a trademark of Japan Electron Optics Ltd., Tokyo, Japan. section of 32 9 6 9 5.6 mm in size, were machined perpendicular to the FSW direction, as indicated in Figure 1.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Our previous work on frictionstir-welded 7075Al-T651 alloy has indicated that cyclic hardening and fatigue life increased with increasing welding speed, but were only weakly dependent on the pin tool rotational rate; the cyclic hardening of the friction-stir-welded joints exhibited a two-stage character. [32] To date, no LCF information of the friction-stirwelded 6xxx-series aluminum alloy is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…He carried out the hardness testing to determine the response of the FSWed specimens to different aging times. Feng et al [5] studied the microstructural changes and cyclic deformation of FSWed AA7075-T651. Su et al [6] investigated the microstructural evolutions of friction stir-processed AA7075-T6 in different regions behind the pin tool.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large number of investigations conducted on the properties of Al7075 joined by FSW [3][4][5][6][7][8], there is almost no work on the FSW of AA7075 with O temper. Almost all the past works on the FSW of AA7075 are pertaining to T6 or T651 condition which exhibits the highest strength before welding.…”
Section: Introductionmentioning
confidence: 99%
“…The 7075 aluminium alloy, in which zinc is the main alloying element, is a precipitation hardened alloy. It is one of the strongest aluminium alloys which is used in many spatial structures and places that require high strength-to-weight ratio [5][6]. Titanium and its alloys have high specific strength and good corrosion resistance and because of these two desirable properties, they have been widely used in the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%